Enactive Approach and Dual-Tasks for the Treatment of Severe Behavioral and Cognitive Impairment in a Person with Acquired Brain Injury: A Case Study - Martínez-Pernía, David; Huepe, David; Huepe-Artigas, Daniela; Correia, Rut; García, Sergio; Beitia, María (Frontiers in Psychology, 2016)
One of the most important sequela in persons who suffer from acquired brain injury (ABI) is a behavioural disorder. To date, the primary approaches for the rehabilitation of this sequela are Applied Behaviour Analysis, Cognitive-Behaviour Therapy, and Comprehensive-Holistic Rehabilitation Programs. Despite this theoretical plurality, none of these approaches focuses on rehabilitating behavioural disorders considering the relation between affordance and environmental adaptation. To introduce this therapeutic view to neurorehabilitation, we apply the theoretical tenets of the enactive paradigm to the rehabilitation of a woman with severe behavioural and cognitive impairment. Over seventeen sessions, her behavioural and cognitive performance was assessed in relation to two seated affordances (seated on a chair and seated on a ball 65 cm in diameter) and the environmental adaptation while she was working on various cognitive tasks. These two seated affordances allowed to incorporate the theoretical assumptions of the enactive approach and to know how the behavior and the cognition were modified based on these two postural settings and the environmental adaptation. The findings indicate that the subject exhibited better behavioural (physical and verbal) and cognitive (matching success and complex task) performances when the woman worked on the therapeutic ball than when the woman was on the chair. The enactive paradigm applied in neurorehabilitation introduces a level of treatment that precedes behaviour and cognition. This theoretical consideration allowed the discovery of a better relation between a seated affordance and the environmental adaptation for the improvement behavioural and cognitive performance in our case study.